A scandal in the British Empire: child guardianship, theosophy, sexuality and fatherhood in Besant v. Narayaniah - Tan, Fidellithy (Nanyang Technological University, 2023)
This MA thesis expands upon existing research into colonial scandal, using a microhistory of the guardianship case involving Jiddu Krishnamurti, Annie Besant and Charles Leadbeater, which took place in twentieth-century colonial Madras and London courts from 1912 to 1914. It explores the hitherto unresearched connections between childhood, sexuality, Theosophy and fatherhood in the case of Besant v. Narayaniah. The thesis argues that this scandal reveals a complex interaction involving colonial contradictions and discussions about colonial boundaries that were emerging at the beginning of the twentieth century. This thesis is structured into four sections, with each chapter centered around a key individual involved in the case: Annie Besant, Charles Leadbeater, Jiddu Krishnamurti, Jiddu Narayaniah. The initial chapter delves into Annie Besant, examining how her self-representation as a maternal figure shaped her positioning as the boys' guardian in court. Her leadership within the Theosophical Society and the esoteric teachings that came to light during legal proceedings played crucial roles in the evolution of the scandal. The second chapter focuses on Charles Leadbeater, investigating how discussions regarding alleged sexual misconduct, homosexuality, and pedophilia were central to concerns of moral decline in colonial India, Australia and metropolitan Britain. The third chapter addresses the negotiations of definitions of childhood, particularly in the context of Jiddu Krishnamurti, delving into the evolving perceptions of childhood and the changing boundaries of age that were subjects of debate within the case. In the final chapter, which centers on Jiddu Narayaniah, Krishnamurti's father, the focus is on the connections between the history of child removal in colonial India and the assertion of patrilineal rights, as well as the role of jurisdiction.